Conservation and Breeding of Apis meIlifera L, in Jayawijaya. Irian Jaya - Firman L Sahwan (Media Konservasi, 1989)
Two subspecies of honeybee identified as Apis mellifica irinica and A. me1li)ku indica were claimed to be the native honeybees of Jayawijaya. They were then confirmed to be a single species :A. mellifera L. Due to the high potential productivity of A. meflifenr and the need to preserve the honeybee's genetic resource, effort to conserve A. meNifera in its natural habitat is suggested.